The eﬀects of ownership structure on corporate value in the Tehran Stock Exchange (TSE) - Hossein Naderi; Sohrab Osta (Management Science Letters, 2012)
In the present study, the separate and simultaneous role of concentration and type of ownership on corporate value is investigated. In this study, the ownership structure is classiﬁed into four classes: the institutional ownership, the corporate ownership, the management ownership and the foreign ownership. In addition, diﬀerent attitudes regarding the above ownership are also tested, that is, active monitoring hypothesis and interest convergence hypothesis. Since, in the sample research no information was found about foreign ownership, this type of ownership was not examined. However, in the case of the other ownerships, a separated hypothesis was developed based on various techniques and their inﬂuence on the corporate value was examined. For each hypothesis, a multiple linear regression model is deﬁned based on the dependent variables. Companies listed in securities exchange commission of Iran makes up the statistical community of present study and the sample consists of 90 companies during 2002-2008. Two types of tests, including correlation test and cross multiple regression test are implemented to examine the hypothesis. Generally, the results reflect no signiﬁcant relationship between the concentration of ownership and the corporate value. The results of the study show that, while there is no relationship between the institutional ownership and management ownership and the corporate value, there is a signiﬁcant relationship between the corporate ownership and the corporate value.